Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(a^2+4\right)^2-16a^2\\ =\left(a^2+4\right)^2-\left(4a\right)^2\\ =\left(a^2-4a+4\right)\left(a^2+4a+4\right)\\ =\left(a-2\right)^2\left(a+2\right)^2\)
Chọn A.
1: \(a^2-4b^2-2a-4b\)
\(=\left(a-2b\right)\left(a+2b\right)-2\left(a+2b\right)\)
\(=\left(a+2b\right)\left(a-2b-2\right)\)
2: \(x^3+2x^2-2x-1\)
\(=\left(x-1\right)\left(x^2+x+1\right)+2x\left(x-1\right)\)
\(=\left(x-1\right)\left(x^2+3x+1\right)\)
a) (a - 2b)x(a + 2b)
b) x2-(y-3)2
=> (x-y+3)(x+y-3)
c) (2a + b - a)(2a + b + a)
=> (a+b)(3a+b)
d) (4(x - 1))2 - (5(x + y))2
⇔ (4x - 4 - 5x - 5y)(4x - 4 + 5x + 5y)
⇔ -(x + 5y + 4)(9x + 5y + -4)
e) (x + 5)2
f) (5x - 2y)2
h) (x - 5)(x2 + 5x + 25)
k) (x + 5)3
Lời giải:
$(a+2b-c)(a+2b+c)-(a^2+4b^2-c^2)=(a+2b)^2-c^2-a^2-4b^2+c^2$
$=(a+2b)^2-a^2-4b^2$
$=a^2+4ab+4b^2-a^2-4b^2=4ab$
\(\left(a-1\right)^2\ge0\Rightarrow a^2+1-2a\ge0\Rightarrow a^2+1\ge2a\left(1\right)\)
\(\left(2b-3\right)^2\ge0\Rightarrow4b^2+9-12b\ge0\Rightarrow4b^2+9\ge12b\left(2\right)\)
\(\left(c\sqrt[]{3}-\sqrt[]{3}\right)^2\ge0\Rightarrow3c^2+3-6c\ge0\Rightarrow3c^2+3\ge6c\left(3\right)\)
\(\left(1\right)+\left(2\right)+\left(3\right)\Rightarrow a^2+1+4b^2+9+3c^2+3\ge2a+12b+6c\)
\(\Rightarrow a^2+4b^2+3c^2+1+9+3\ge2a+12b+6c\)
\(\Rightarrow a^2+4b^2+3c^2+13\ge2a+12b+6c\)
\(\Rightarrow a^2+4b^2+3c^2\ge2a+12b+6c-13\)
mà \(2a+12b+6c-13>2a+12b+6c-14\)
\(\Rightarrow a^2+4b^2+3c^2>2a+12b+6c-14\)
\(\Rightarrow dpcm\)
a) Ta có: \(M=-x^2-4x+20\)
\(=-\left(x^2+4x-20\right)\)
\(=-\left(x^2+4x+4-24\right)\)
\(=-\left(x+2\right)^2+24\le24\forall x\)
Dấu '=' xảy ra khi x=-2
1: 2a+2b=2(a+b)
2: 2a+4b+6c
=2*a+2*2b+2*3c
=2(a+2b+3c)
3: \(-7a-14ab-21b=-7\left(a+2ab+3b\right)\)
4: \(2ax-2ay+2a=2a\left(x-y+1\right)\)
5: \(=3a\cdot ax-3a\cdot2ay+3a\cdot4=3a\left(ax-2ay+4\right)\)
6: \(=2\cdot2ax-2\cdot ay-2\cdot1=2\cdot\left(2ax-ay-1\right)\)
7: =a^2-(2b)^2
=(a-2b)(a+2b)
8: =(5a)^2-1^2
=(5a-1)(5a+1)
9: =9(16a^2-9)
=9(4a-3)(4a+3)
\(\left(a^2+4b^2\right)^2-16a^2\)
\(=\left(a^2+4b^2-4a\right)\left(a^2+4b^2+4a\right)\)
p/s: chúc bạn học tốt
(a^2+4b^2)^2-16a^2
=(a^2+4b^2-4a)(a^2+4b^2+4a)